Strategic narratives in climate change: Towards a unifying narrative to address the action gap on climate change. (June 2017) - Bushell, Simon; Buisson, Géraldine Satre; Workman, Mark; Colley, Thomas
Abstract: There is a significant 'action gap' between what scientists argue is necessary to prevent potentially dangerous climate change and what the government, industry and public are doing. This paper argues that a coherent strategic narrative is key to making meaningful progress. It does this by first analysing a number of narratives which have been used to try and create audience buy-in on the need for action on climate change, and those that argue that no action needs to be taken. A framework is then proposed for how compelling and unifying strategic narratives on climate change might be constructed. It is suggested that the unifying strategic narrative could address the complex range of actors who need to be engaged, provide a coherent explanation for government strategy, and harness the drivers of behavioural change needed to meet the challenge. Research into climate change strategic narratives is nascent, but the authors believe that there is much to be gained from pursuing and intensifying this research.